Fil-Am brings girl power to Guns N' Roses (2018)
Melissa Reese is being celebrated in rock circles as the first and only female member of the iconic American rock band Guns N' Roses (GnR). and She's half-Filipina.
For more details visit us at UP College of Music Library.